INDUSTRIAL AND SECTORAL MODELS OF INNOVATIVE DEVELOPMENT OF SOCIO-ECONOMIC SYSTEMS - E. Shatskaya (Вестник Северо-Кавказского федерального университета)
The purpose of the article is a theoretical and methodological generalization of the features of the development of socio-economic systems in modern conditions. The specific features and new management mechanisms influencing the transformation of the development of socio-economic systems have been identified. An analysis of the research has been carried out, as a result ofwhich it has been established that it is possible to use in practice several models of the development of socio-economic systems at once, the role of innovative development has been substantiated. The article has arguably proved that in modern conditions new templates are superimposed on the sectoral structure that determine the attributes of uniication, which do not correspond to the contours of traditional classiications, but form new communities, determining innovative trends.